Investigating the application of “Guttmann Cognitest”® in older adults and people with acquired brain injury - Cattaneo, Gabriele; Roca-Ventura, Alba; Heras, Eva; Anglada, Maria; Missé, Jan; Ulloa, Encarnació; Fankhauser, Simon; Opisso, Eloy; García-Molina, Alberto; Solana-Sánchez, Javier (Frontiers in Neurology, 2024)
Introduction Digital solutions for cognitive assessment are currently not only widely used in experimental contexts but can also be useful in clinical practice for efficient screening and longitudinal follow-up. The “Guttmann Cognitest”®, which includes seven computerized tasks designed to assess main cognitive functions, revealed in a previous validation study to be a potential useful tool to assess cognitive functioning in healthy middle-aged adults. Method Here, we present results from a validation in two different populations: one consisting of older adults, and the other comprising young and middle-aged individuals, some of them affected by acquired brain injury. To perform a convergent validity test, older adults were also administered with the MOCA, while young and middle-aged individuals were administered with a short neuropsychological assessment including gold-standard neuropsychological tests. We also conducted sensitivity and specificity analysis to establish the utility of this instrument in identifying potential cognitive dysfunctions in the two groups. Results Results demonstrated strong convergent validity as well as good specificity and sensitivity characteristics. Discussion This tool is a valid and useful instrument to assess cognitive functioning and detecting potential cases of cognitive dysfunctions in older adults and clinical populations.